Pemodelan Proses dan Evaluasi Ekonomi Produksi Bio-Oil dari Limbah Tandan Kosong Kelapa Sawit - Fanany, Muhammad Rifki; Septhian Marno; Tirto Prakoso; Aqsha Aqsha; Astri Nur Istyami; Meiti Pratiwi; Indarto, Antonius (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Oil palm empty fruit bunches (OPEFB) are solid waste which is the residue from processing palm oil into crude palm oil (CPO). The high number of OPEFB produced requires proper handling to minimize the negative impact on the surrounding environment. One of the solutions to deal with this is to process OPEFB into bio-oil using fast pyrolysis technology. Before applying the process in the real world, it is necessary to do an economic evaluation first to find out whether the process can be economically profitable. This study aims to carry out an economic evaluation of the bio-oil production process made from OPEFB using fast pyrolysis technology. Aspen Plus was used in this study to carry out process modeling, while the economic evaluation was based on several literatures such as previous books and journals. Based on the results of the economic evaluation, the total capital cost (TCC) required to build this facility is USD 1,152,686 with an operating expenditure (OpEx) of USD 168,107. Then, from the economic indicators in the form of payback period (PBP) and internal rate of return (IRR), this facility takes 4 years to reach PBP with an IRR of 22%.